2009
DOI: 10.3742/opem.2009.9.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of Eriocaulon sieboldianum through the activation of caspase-3 in human leukemia cell line, HL-60 cells

Abstract: Eriocaulon sieboldianum (ES) is used in traditional oriental medicine for various medicinal purposes including headache, toothache, and inflammation. However, the anti-cancer effect of the ES is still not fully understood. In the present study, the human leukemia cell line HL-60 was used to characterize the apoptotic effects of ES. ES induced cytotoxicity of HL-60 cells in a doseand time-dependent manner. ES induced the generation of reactive oxygen species, and the release of cytochrome c in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This species can be found in Bangka Belitung Island, Indonesia, and traditionally, this herb is used by the local people for cancer prevention. E. cinereum has not been intensively studied for their property as anticancer compared to other genus of Eriocaulon [9][10][11][12]. The finding of the antiproliferative activity of the ethanol extract of E. cinereum in HeLa cells from our preliminary study [13] led to our further investigation to evaluate the cytotoxic activity of E. cinereum against HeLa cell lines.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This species can be found in Bangka Belitung Island, Indonesia, and traditionally, this herb is used by the local people for cancer prevention. E. cinereum has not been intensively studied for their property as anticancer compared to other genus of Eriocaulon [9][10][11][12]. The finding of the antiproliferative activity of the ethanol extract of E. cinereum in HeLa cells from our preliminary study [13] led to our further investigation to evaluate the cytotoxic activity of E. cinereum against HeLa cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Eriocaulon australe from China has cytotoxic activity against A549 lung cancer cells, MCF-7 breast cancer cells, and HeLa cervical cancer cells [9]. Meanwhile, Eriocaulon sieboldianum was reported to exhibit cancer activity against HL-60 human leukemia cell line [10] and induce cell cycle arrest of human liver cancer cells HepG2 [11]. Furthermore, Fan et al also reported antitumor activity against K562 leukemia cells from E. sieboldianum [12].…”
Section: Introductionmentioning
confidence: 99%